2017
DOI: 10.3389/fevo.2017.00131
|View full text |Cite
|
Sign up to set email alerts
|

Half-Blind to the Risk of Predation

Abstract: Blinking serves several functions in animals, but it comes at the cost of intermittent blindness. Blinking can occur spontaneously, but it is commonly associated with head movements. As feeding animals often need to move the head down repeatedly to gather resources, intermittent blindness might represent a hitherto unappreciated cost of feeding. In addition, this cost might also be more prevalent in larger groups as feeding effort typically increases with group size. In chickens (Gallus gallus domesticus), bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Blinking impairs visual processing in humans (Volkmann et al, 1980;Bristow et al, 2005;Hoppe et al, 2018) but no empirical studies have tested whether it also impairs visual processing in birds or other species. However, indirect evidence suggests that blinking behavior in birds interferes with visual processing because (1) birds strategically inhibit their blinks (Cross et al, 2013;Yorzinski, 2016;Beauchamp, 2017) and (2) the nictitating membrane used for blinking is only semi-transparent in many avian species (Sivak, 1980). We tested the influence of wind on blinking behavior using captive great-tailed grackles (Quiscalus mexicanus), a songbird species that often inhabits open areas and is native to North and South America (Johnson and Peer, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blinking impairs visual processing in humans (Volkmann et al, 1980;Bristow et al, 2005;Hoppe et al, 2018) but no empirical studies have tested whether it also impairs visual processing in birds or other species. However, indirect evidence suggests that blinking behavior in birds interferes with visual processing because (1) birds strategically inhibit their blinks (Cross et al, 2013;Yorzinski, 2016;Beauchamp, 2017) and (2) the nictitating membrane used for blinking is only semi-transparent in many avian species (Sivak, 1980). We tested the influence of wind on blinking behavior using captive great-tailed grackles (Quiscalus mexicanus), a songbird species that often inhabits open areas and is native to North and South America (Johnson and Peer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We tested birds when their heads were restrained and unrestrained. Because blinks are often associated with head movements in other species (Evinger et al, 1994;Gandhi, 2012;Yorzinski, 2016;Beauchamp, 2017), we wanted to test the impact of windy conditions on blinking behavior while controlling for the possible confounding effects of head movements. We expected that the birds' blinking behavior would increase when they were exposed to the simulated wind.…”
Section: Introductionmentioning
confidence: 99%
“…Their blinking behavior was generally similar regardless of whether the birds' heads were restrained or not. Previous work has found that birds (Beauchamp, 2017;Yorzinski, 2016) and…”
Section: Discussionmentioning
confidence: 98%
“…Their blinking behavior was generally similar regardless of whether the birds’ heads were restrained or not. Previous work has found that birds (Beauchamp, ; Yorzinski, ) and primates (Evinger et al, ; Gandhi, ) often blink when they move their heads, so it was possible that the grackles would have exhibited increased blinking behavior when their heads were unrestrained. However, the grackles did not necessarily exhibit many head movements even when their heads could move freely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation